Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2427.2011.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

Centennial-scale changes to the aquatic vegetation structure of a shallow eutrophic lake and implications for restoration

Abstract: 1. We investigate long-term (>200 years) changes to the composition and spatial structure of macrophyte communities in a shallow, eutrophic lake (Barton Broad, eastern England) and consider the implications for lake restoration. 2. Historical macrophyte data were assembled from a variety of sources: existing plant databases, museum herbaria, journal articles, old photographs and eyewitness accounts. Additionally, two types of sediment core sample were analysed for plant macro-remains and pollen; bulk basal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Changes in a lake's aquatic vegetation can be determined from historical botanical data yet, with a few exceptions (Sand-Jensen 1997;Davidson et al 2005;Madgwick et al 2011;Dudley et al 2012), such records rarely exist for time periods (decades to centuries) sufficient to assess human impacts. An alternative, or indeed complementary, tool for assessing long term changes in vegetation is the palaeoecological record.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in a lake's aquatic vegetation can be determined from historical botanical data yet, with a few exceptions (Sand-Jensen 1997;Davidson et al 2005;Madgwick et al 2011;Dudley et al 2012), such records rarely exist for time periods (decades to centuries) sufficient to assess human impacts. An alternative, or indeed complementary, tool for assessing long term changes in vegetation is the palaeoecological record.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the taphonomic issues associated with the plant-macrofossil relationship arising from the varying reproductive strategies and dispersal capabilities of plants, several comparative studies of macrofossil records with botanical records have shown plant macrofossils to reliably record shifts in the dominant aquatic vegetation of shallow lakes (Davidson et al 2005;Salgado et al 2010;Clarke et al 2014;Levi et al 2014). Plant macrofossils have been variously employed to investigate long-term successional changes in the submerged vegetation of lakes (Bradshaw et al 2005;Rasmussen and Anderson 2005), responses to recent eutrophication (McGowan et al 2005;Salgado et al 2010;Sayer et al 2010a;Madgwick et al 2011) and top-down impacts of fish (Sayer et al 2016), and to inform on lake conservation status and the need for appropriate management (Sayer et al 2012;Wiik et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that plant remains from different species have different distributions within lake basins (Davidson et al 2005;Zhao et al 2006;Salgado et al 2010;Madgwick et al 2011). Clarke et al (2014) recommend that cores therefore be taken close enough to the shore of a lake to pick up as many remains as possible, but not so close that the sediment profile is disturbed.…”
Section: Implications For Paleolimnologymentioning
confidence: 99%
“…Monitoring data from such periods are usually scarce or non-existent, with some exceptions (Egertson et al, 2004;Hargeby et al, 2007;Sand-Jensen et al, 2008;Hilt et al, 2013;Hobbs et al, 2014). In situation without reliable long-term monitoring data, studies into historical ecosystem state can be supported by paleolimnological analyses (Battarbee et al, 2005;Sayer et al, 2010a;Madgwick et al, 2011;Kowalewski et al, 2013Kowalewski et al, , 2015. This particularly concerns shallow lakes distinguished by abundant development of macrophytes accompanied by a rich invertebrate fauna, and providing conditions favourable for the deposition of macrofossils (Rawcliffe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%